From grassroots to digital ties: A case study of a political consumerism movement. (July 2014) - Parigi, Paolo; Gong, Rachel
New grassroots organizations that target ethical consumer choices and behavior represent a departure from traditional social movement organizations. In this article, we study the activists of one of these organizations and show that social network ties formed mainly online greatly reinforce commitment toward the goals of the movement. We suggest that online ties, that is, digital ties, are important for political consumerism movements because they create audiences for private actions. It is because of the presence of these audiences that the individual participants can reinterpret their actions into public ones. We used an online survey to collect data on the users of the Transition US social website on Ning.com. Over half of the respondents have experiences with political activism. However, their responses indicate that they are dissatisfied with traditional means of political participation (e.g. rallies) and prefer non-contentious collective actions (e.g. local gardening). Respondents perceive community organizing to be the most effective way to bring about social change, deprioritizing connections to local government. Furthermore, respondents who formed digital ties with other activists were significantly more likely than respondents who had no ties with other activists to adopt consumer changes consistent with the goals of the movement. We interpreted this finding as an indicator that digital ties share some of the characteristics of strong ties, and we explored this similarity in this article.